2015
DOI: 10.3758/s13414-015-0918-1
|View full text |Cite
|
Sign up to set email alerts
|

Automatic capture of attention by conceptually generated working memory templates

Abstract: Many theories of attention propose that the contents of working memory (WM) can act as an attentional template, which biases processing in favor of perceptually similar inputs. While support has been found for this claim, it is unclear how attentional templates are generated when searching realworld environments. We hypothesized that in naturalistic settings, attentional templates are commonly generated from conceptual knowledge, an idea consistent with sensorimotor models of knowledge representation. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…People are slower to respond on a visual search task when an item matching an item held in working memory is presented as a distractor (attentional capture). A broad range of mental states and processes can bias our attention, including visual working memory, verbal working memory, long‐term memory, associative knowledge, implicit memory, and reward . Studies have found converging evidence for attentional capture when the working memory load is held to a single item (although see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…People are slower to respond on a visual search task when an item matching an item held in working memory is presented as a distractor (attentional capture). A broad range of mental states and processes can bias our attention, including visual working memory, verbal working memory, long‐term memory, associative knowledge, implicit memory, and reward . Studies have found converging evidence for attentional capture when the working memory load is held to a single item (although see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…As this latter finding suggests, then, VWM can be used deliberately to prioritize the averaging of prespecified items through memory-driven selection. What is particularly interesting about this finding, though, is that this form of attentional guidance can also occur incidentally as simply maintaining a feature value in VWM can bias attention toward perceptually similar information in the visual field (e.g., Carlisle & Woodman, 2011;Hollingworth et al, 2013;Kumar et al, 2009;Olivers et al, 2006;Soto et al, 2005;Sun et al, 2015). This begs the question, then, does memory-driven selection automatically alter the contribution of individual items to perceptual averages even when it is costly to do so (i.e., when all items are equally relevant to one's task)?…”
mentioning
confidence: 99%
“…Sixty native Chinese students from Zhejiang University, randomly divided into three groups, completed Experiment 1 for either a course credit or 15 RMB. Sample size (20) was estimated based on a medium effect size (η 2 = .40) from previous studies using a similar paradigm (e.g., Olivers, 2009;Sun et al, 2015), and maintained constant across experiments. All participants provided informed consent, and all procedures were approved by the Institutional Review Board at Zhejiang University.…”
Section: Participantsmentioning
confidence: 99%